Koncepcja przekładu L’ubomira Feldka w kontekście słowackiej myśli przekładoznawczej - Spyrka, Lucyna (Przekłady Literatur Słowiańskich, 2016)
Lubomír Feldek’s concept of translation in the context of the Slovak translatological thoughts In Poland, Slovak translatological thought is mainly associated with the concepts of Anton Popovič and his school of translation. The article presents an overview of the history of the development of translation and translation studies in Slovakia, and then discusses the poet Lubomír Feldek’s concept based on his practical experiences as an interpreter and critic of translation. Feldek, like Popovič treats translation as a form of communication, emphasizing a focus on the issues of reception. He presented his conception in the book Z reči do reči (1977), which was met with great interest by Slovak theoreticians of translation. The article presents the polemical and critical opinions and acceptance and praise which were formulated at the time of the publication of the Feldek’s book, and the comments subsequent to the most recent controversy, which document the place of the views of the poet — translator in Slovak translatology. Key words: the theory of translation, Slovak translatology, Ľubomír Feldek, history of translation